Physicochemical characterization of water-soluble chitosan derivatives with singlet oxygen quenching and antibacterial capabilities - Vanden Braber, Noelia Luciana (2017)
New water-soluble chitosan derivatives (WSCh) were obtained by Maillard reaction (MR) between glucosamine (GA) with both low and medium molecular weight chitosans (Ch). The WSCh showed larger solubility than the respective Ch, while their deacetylation degree (DD) decreased by approximately 12%. Infrared spectroscopy experiments of WSCh confirmed the formation of imine bonds after MR with intensified pyranose structure, and sugar molecules as polymer branches. However, a 6-times reduction of the molecular weight of WSCh was measured, indicating the breakdown of the polysaccharide chain during the MR. The polysaccharides quenched singlet molecular oxygen (1O2), with rate quenching constants correlating with the DD value of the samples, suggesting the important role of amino groups (−NH2) in the deactivation of 1O2. Additionally, all polysaccharides presented antimicrobial activity against pathogenic bacteria, e.g. Staphylococcus aureus, Escherichia coli, Salmonella sp., Enterococcus faecalis and Listeria ivanovii, as tested by their minimum inhibitory concentration (MIC). This way we obtained new water-soluble polysaccharides, with similar functional properties to those presented by native Ch, enhancing its potential application as carrier material for bioactive compounds.